(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to determine the impact of employer branding on job application rates, focusing on the role of corporate reputation as a mediator. The subjects of this study consisted of a sample of 131 Generation Z students in Semarang who were about to enter the workforce. Participants were recruited using purposive sampling. Data were collected using a questionnaire, and data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS version 3.2.9. The results show that employer branding has a significant impact on overall corporate reputation. The impact of corporate reputation on the intention to apply for a job is also seen in the results of the study. And the impact of employer branding on the intention to apply for a job on work-ready generation Z students in Semarang will be more influential when there is corporate reputation as a mediator. Based on this research, organisations or companies need to take into account the importance of forming a positive image, which serves as a marketing strategy for employer branding to attract the best/potential job applicants.